PEMBERDAYAAN GURU DAN DOSEN SEBAGAI TENAGA PROFESIONAL - Hermanto Nst, Mulyadi (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2021)
Teacher and this lecturer as professional energy aim to to execute system education of national, upgrading and realizing the target of education of national, that is expanding educative participant potency it in order to become godfearing and religious human being to God Which Single The most have, august to behavior, healthy, bookish, capable, creative, self-supporting, and also become democratic citizen and hold responsible. Role of lecturer and teacher occupy very strategic position, that is: a) reconditional Agent; b) as fasilitator creating condition learn in child x'self; c) Be in control of creation result of learning educative subjek; d) for example byword; e) Hold responsible professionally improve its ability; and f) Respect code of etik professional.